2022
DOI: 10.1785/0220210078
|View full text |Cite
|
Sign up to set email alerts
|

A New Set of Automated Methodologies for Estimating Site Fundamental Frequency and Its Uncertainty Using Horizontal-to-Vertical Spectral Ratio Curves

Abstract: This study proposes a new set of methodologies to estimate the site fundamental frequency using the horizontal-to-vertical spectral ratio (HVSR) of recorded surface ground motions. Because of the lack of consensus in HVSR calculation among researchers, a wide range of methods are practiced in this area, yielding different site fundamental frequencies at a given site due to analyst subjectivity. In this study, current practices for combining horizontal components—geometric mean and RotD50—are examined first, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Figure 2 illustrates an example for estimating f ml , A ml , σ ln ( f ml ) , and σ ln ( A ml ) at Palmdale Fire Station using Method 1. The explanation, limitations, and application of the automated methods are discussed in detail by Yazdi et al (2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 illustrates an example for estimating f ml , A ml , σ ln ( f ml ) , and σ ln ( A ml ) at Palmdale Fire Station using Method 1. The explanation, limitations, and application of the automated methods are discussed in detail by Yazdi et al (2022).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the amplitude of the peak in HVSR is likely to be less than the actual amplification factor. Yazdi et al (2022) further showed that the amplification factors obtained from the average HVSR of the site are generally smaller than the ones obtained from individual HVSR curves because the peak does not always occur at exactly the same frequency. Hence, using average HVSR curves results in smaller amplification factors.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Note that prior researchers, such as Yee et al (2013) and Afacan et al (2019), have demonstrated the importance of shear strength in the modeling of site response at large strains and that researchers, such as Yee et al (2013) and Groholski et al (2016), have provided methods to adjust the backbone curve to account for it. Finally, another key aspect of this work is to quantify site response uncertainty using both the actual recordings at a geotechnical downhole array (Yazdi et al, 2022; Yee et al, 2013; Zogh et al, 2021) and the predicted median response spectra for different levels of intensity to assess the reliability of using the predicted median response spectra in case the actual recordings at the location of site are not available.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic uncertainty of ground motions affects earthquake engineering disciplines, such as the performance-based post-earthquake assessment and decision-making (Aghababaei et al, 2021; Roohi and Hernandez, 2020; Weatherill et al, 2015). Several studies attempted to quantify and model this randomness in various seismic problems (Alamilla et al, 2001; Wen et al, 2003; Yazdi et al, 2022). In this study, we focus on quantifying the uncertainty and validity of the generated motions using the GPR model introduced by Tamhidi et al (2021).…”
Section: Introductionmentioning
confidence: 99%